From the desired innovation to realistic innovation. Schools changed by ICT - Montero, Maria Lourdes; Gewerc, Adriana (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
Here we present results from two research projects. The aim of both was to analyze the implicated factors, strengths and weaknesses that are generated when addressing educational innovation projects which focus on the promotion of new education environments and learning mediated by ICT. The theoretical and methodological approach reflects a collaborative action-research perspective and is articulated as a longitudinal case study involving four schools from different types: Integrated Public School (CPI), Secondary Education School (IES); Rural Cluster Center (CRA); Early Years and Primary Education School (CEIP). The data were analyzed using the following dimensions: socio-political context; teaching staff and institution. Such dimensions were extracted from the theoretical framework of the research and also emerged from the reality under study. The following are among the most relevant conclusions: 1. Schools and teaching staff are faced with a dilemma between their traditional role as conservators of the most significant cultural features and pressures for innovation deriving from the conditions of the new economy. 2. ICT are being used as a political instrument of the innovation discourse but at the same time are used to maintain school culture as well as contents and teaching methodologies fixed. 3. The scant change in school culture influences the maintenance of the status quo, and limits the value of ICT for the mobilization of teaching and learning conditions. 4. The existing atmosphere in schools reveals anxiety over teachers’ lack of time to think, reflect, implement and assess the changes that would be possible using different versions of ICT.